2015
DOI: 10.1159/000375435
|View full text |Cite
|
Sign up to set email alerts
|

Warburg Effect or Reverse Warburg Effect? A Review of Cancer Metabolism

Abstract: Cancer is a major threat to human health. A considerable amount of research has focused on elucidating the nature of cancer from its pathogenesis to treatment and prevention. Tumor cell metabolism has been considered a hallmark of cancer. Cancer cells differ from normal cells through unlimited cell division, and show a greater need for energy for their rapid growth and duplication. Research on glycometabolism, as the key point of energy metabolism, has played a unique role. In the 1920s, Warburg found that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
141
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 38 publications
1
141
0
Order By: Relevance
“…These results indicate that miR-125b-induced deregulation of glucose metabolism is not a typical Warburg effect. However, metabolic plasticity and metabolic heterogeneity have been found in some cancers with aggressive phenotype [4046]. It also has been reported that aerobic glycolysis is less active in T-ALL cells than normal T cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that miR-125b-induced deregulation of glucose metabolism is not a typical Warburg effect. However, metabolic plasticity and metabolic heterogeneity have been found in some cancers with aggressive phenotype [4046]. It also has been reported that aerobic glycolysis is less active in T-ALL cells than normal T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past couple of decades, advances in technology have allowed mitochondrial function to be studied in a far greater detail, and it is now realised that cancer cells have active and functional mitochondria, contrary to Warburg's theory [13,14]. In the last decade, research has shown that different tumour types (and indeed subpopulations within a tumour) have different bioenergetic alterations.…”
Section: The Warburg Effectmentioning
confidence: 99%
“…Mechanistically, LDHA depletion results in downregulation of p21 and Bax, and upregulation of cyclin D and Bcl2, which contributes to growth arrest; moreover, si-LDHA results in MMPs downregulation, facilitating blockage of cell migration and invasion in vitro. Therefore, our findings demonstrated that LDHA, an oncogene contributed to the Warburg effect [8,14] , had a drastic implication on tumor development and progression in renal cancer.…”
Section: Discussionmentioning
confidence: 73%
“…The Warburg effect, also known as aerobic glycolysis [8] , is a hallmark of tumor cell metabolism [8][9][10][11][12] , which is described by the increased glucose uptake and the lactate production in tumor cells even under normal oxygen concentrations. Until recently, the important function of aerobic glycolysis in tumor development has been widespread and palpably recognized [13] .…”
mentioning
confidence: 99%